Ethnomathematics in Oko Mama Woven Craft of the Amanuban Community: A Geometric Study - Taneo, Prida N. L.; Turmudi; Nurlaelah, Elah; Fatimah, Siti (Pendidikan Matematika UNIMOR, 2025)
Mathematics is often perceived as a challenging subject by students, necessitating innovative instructional approaches that enhance conceptual understanding and contextual relevance. The ethnomathematics approach presents a valuable strategy by linking mathematical ideas to cultural practices, thus fostering more meaningful learning. This study focuses on exploring mathematical concepts embedded in the oko mama plaiting craft tradition of the Amanuban community in South Central Timor. Through a qualitative design with an ethnographic method, the research involved direct engagement with three local artisans selected purposively based on their expertise. Data collection was conducted through semi-structured interviews, field observations, and documentation, followed by triangulation to ensure data validity. The analysis uncovered a variety of geometric concepts found in the artisans’ practices. These include two-dimensional shapes such as squares, rectangles, parallelograms, rhombuses, triangles, trapezoids, and both regular and irregular hexagons and three-dimensional forms such as cubes, rectangular prisms, triangular prisms, and hexagonal prisms. Mathematical ideas involving perimeter, area, and volume also emerged through the measurement and structuring techniques used in plaiting. The study demonstrates that local cultural practices serve not only as expressions of heritage but also as rich sources of mathematical thinking. Findings highlight the potential of the oko mama craft to serve as a contextual learning resource for geometry education. This research contributes to the existing body of knowledge by offering a more comprehensive ethnomathematical analysis compared to earlier studies that focused narrowly on basic geometric forms and calculations.